Light-driven liquid metal nanotransformers for biomedical theranostics - Svetlana A. Chechetka (Nature Portfolio, 2017)
Liquid metals are excellent candidate materials for biomedicine, owing to their intriguing optical properties and chemical stability. Here, the authors design multifunctional theranostic liquid metal nanocapsules that, upon irradiation, generate heat and reactive oxygen species and change shape to release drugs.